Concept of Moral and Character of Professional Doctor in Islam - Sumin, Syari; Peviyatmi, Peviyatmi; Risnaldi, Risnaldi (Khalifa Journal of Islamic Education, 2017)
This article is aimed at discussing the concept of moral and character of professional doctor pursuant to Islamic perspective. Method used for the study is content analysis, an approach in qualitative research. Data was obtained through reading of various theories and postulates proposed by experts and previous researches regarding to profession of doctors in Islamic perspectives. The data was collected, reduced, presented, and ended with a conclusion of thematic analysis approach. It is found that there are nine characters of an ideal doctor pursuant to Islamic perspective, namely, i) possessing good Aqeedah and embracing true faith, ii) being sincere and diligent in performing work, iii) skillful in his profession and specialization, iv) being honest in attitude and work, v) sensitive and caring, vi) raising optimism for patients, vii) stylish and respectful, viii) possessing good moral and noble characters, ix) and being respectful, helpfulÂ  and humble. The article is expected to be references for Muslim doctors and medical practitioners as well as to be an idea of other researchers to develop the study regarding to the identical issues yet in different context.Â